Optimizing Employee Performance through Ability, Discipline, Motivation, and Occupational Health and Safety Management - Wilchan Robain; Ramadhan Harahap; Sally Syahfitri (International Journal of Management, Economic and Accounting, 2025)
This study aims to analyze the influence of ability, work discipline, and work motivation on employee performance by incorporating Occupational Health and Safety (OHS) management elements. The research employed a quantitative approach with a population and sample of 53 employees. Data were collected through a structured questionnaire that had been tested for validity and reliability. The analysis results indicate that ability, work discipline, and work motivation have a positive and significant effect on employee performance. Furthermore, the implementation of OHS management enhances employees’ work effectiveness by improving workplace comfort and safety. These findings underscore the importance of strengthening competence, rule compliance, work motivation, and OHS implementation to achieve optimal employee performance.